INVASIVE ASPERGILLOSIS IN AN ADOLESCENT - M. E. Makogonova; A. S. Maletin; E. A. Desyatik; N. N. Klimko; A. Yu. Mushkin (Туберкулез и болезни лёгких)
The article presents the clinical case of invasive aspergillosis in a 15-year-old adolescent with lesions in the spine, ribs and both lungs, and primary immune deficiency which was not diagnosed earlier. In order to diagnose this disease it was necessary to differentiate it from the generalized form of tuberculosis and to perform integral X-ray examination and surgery with consequent morphological and bacteriological examination of the surgical samples.